Does market oriented environmental sustainability determine the export performance? A study of leather products manufacturing SMEs in India - Syed Khusro Chishty; Sonia Sayari (Cogent Business & Management, 2024)
Market-oriented environmental sustainability (MES), which is part of an organization's orientation towards the export market and its impact on the export resources and competencies of firms was analyzed in this study. Further, this research also examines the influence of export resources and competencies on export strategy of marketing and export performance of organizations. To accomplish this objective, structural equation modeling (SEM) was used. Data was gathered from 194 manufacturing export enterprises. The results indicate that MES positively impacts resources and competencies connected to green export. Furthermore, only resources indirectly affect eco-friendly export marketing strategy through capabilities, but green export-related competencies directly affect it. The findings also demonstrate how an eco-friendly export marketing approach improves a company's export success. By analyzing business orientation and its impact on eco-friendly export marketing strategy and export performance, this research contributes the field of sustainability and exporting. This study has significant managerial Implications, it explicitly opens up significant decision-making channels for Indian SMEs engaged in exporting to various markets. First, it advises businesses that their acquisition of resources and eventual development of skills will be influenced by their orientation, i.e. preference for green values, norms, and behaviors. The study's findings also demonstrate that businesses must put effort into developing capabilities rather than just investing in resources alone.
Keywords: 650; Green exporting; Mes; export marketing orientations; export marketing strategy; exporting processes; export performance